Persepsi Mahasiswa terhadap Penggunaan Meta AI sebagai Sumber Informasi untuk Tugas Akademik - Wulandari, Anggi Kurnia; Asmara, Rini (Lembaga Yasin AlSys, 2025)
This research is based on the tendency of Library and Information Science students to use Meta AI as an information source, raising questions about its effectiveness, efficiency, benefits, and usefulness. The purpose of this study is to describe the perceptions of Library and Information Science students regarding the use of Meta AI as an information source for academic tasks. This research employs a descriptive quantitative research method. The subjects of this study are Library and Information Science students at Padang State University who entered in 2021, 2022, and 2023. The sample consists of 73 respondents selected using purposive sampling technique. The theoretical framework used in this research is the Technology Acceptance Model (TAM). Data analysis results show that the perceived usefulness indicator of Meta AI received an average score of 2.97, while the perceived ease of use indicator received an average score of 3.11. Therefore, the overall perception of usefulness and ease of use of Meta AI received a score of 3.04, placing it in the good category. Based on the overall average score, it can be concluded that Library and Information Science students have a positive perception of using Meta AI as an information source for academic tasks.